Hubungan antara langkah-langkah penjagaan kesihatan dengan latar belakang diri individu semasa kejadian bencana jerebu - Mogan, Periasamy (2017)
The haze situation in Malaysia is a disaster that cannot be avoided because it is cross border. Up to now, measures of health care by the community members themselves are still unclear and seemed less effective. This is evident because whenever haze episodes occur, there are still problems involving respiratory illnesses or refusal to comply with the advice of health care provider as outlined by the Ministry of Health Malaysia. The objectives of this study are to examine the level of health care, the relationship between backgrounds of individuals with personal health care and to assess the differences in backgrounds of individuals with health care during the haze disaster. This study involved 384 respondents using quantitative method through three different techniques, namely descriptive analysis, Pearson correlation and one way ANOVA. The study found that the level of health care during the haze disaster in the study area is good but there are still individuals who do not comply with health care measures recommended by the government, including refusing to wear face masks. In addition, the relationship analysis showed that all constructs under the individual background such as age, number of family members, income and length of stay were significantly related to the level of 0.01 and 0.05 to construct measures of health care during the haze disaster. Meanwhile, analysis of variance found that all four constructs under the individual background namely age, number of family members, income and type of residence showed that there are differences in measures of health care during the haze disaster. In contrast, there are only one construct under the individual background that shows no difference to health care measures during the haze disaster which is duration of stay. This shows that the duration of stay in an area does not guarantee a difference to healthcare during haze disaster. Therefore, to ensure public safety during haze disasters, both the government and the public sectors must work together to deal with this problem. In this case, the public sector must comply with all the recommendations issued by the government for mutual interest.